THE USE OF QUALITY MANAGEMENT TOOLS AND THE ISSUE OF DOCUMENT ARCHIVE MANAGEMENT IN PUBLIC AGENCIES - Barbosa Machado, Lilian Andréia; Rodolpho , Daniela (Revista Interface Tecnológica, 2022)
This article aims to identify possible solutions to a problem that affects different areas within the public sector, with regard to the uncontrolled use of paper files. We are going through an era in our society where the growing scarcity of resources and the need to use them efficiently and consciously are widely known, avoiding misuse and waste of materials, such as paper, natural resources, means of production, necessary capital for maintenance, the physical space for storage and, finally, the work and energy for, at the end of its useful life, its purge. And we still have to consider that the state has the responsibility to promote sustainability. The excessive use of paper causes several impacts within the corporate environment, with the physical space being one of the most difficult to be solved, in addition to the expenditure of financial resources to purchase the material. Thus, it is necessary to find ways and tools that help contain and resolve the issue; The article consists of a case study based on a bibliographic review and theoretical framework, where the proposal is the use of quality tools to minimize the problem through the application of Brainstorming theory and PDCA methodology for a document organization with virtual digitization programs.
Keywords: Archive; Brainstorming; PDCA Cycle; Quality